A Case of Mycobacterium kansasii Pulmonary Disease Presenting as Endobronchial Lesions in HIV-Infected Patient - Kim, Moon Sung; Han, Ji Won; Jin, Su Sin; Lee, Jong Min; Hah, Jick Hwan; Kim, Youn Jeong; Kim, Seung Joon; Kang, Moon Won; Kang, Ji Young (Tuberculosis and respiratory diseases, 2013)
Incidence of nontuberculous mycobacterium (NTM) pulmonary disease is increasing with the wider recognition and development of diagnostic technology. Mycobacterium kansasii is the second most common pathogen of NTM pulmonary disease in human immunodeficiency virus (HIV)-infected patients. However in Korea, the incidence of M. kansasii pulmonary disease is relatively low, and there has been no report of M. kansasii pulmonary disease with bronchial involvement in HIV patients, to the best of our knowledge. We report a case of M. kansasii pulmonary disease presenting with endobronchial lesions in an HIV-infected patient complaining of chronic cough with bilateral enlargements of hilar lymph nodes on chest X-ray.